Developing cyber-bullying knowledge and awareness instrument (CBKAi) to measure knowledge and perceived awareness towards cyber-bullying among adolescents / Nadia Abdul Wahab and Wan Ahmad Jaafar Wan Yahaya - Abdul Wahab, Nadia; Wan Yahaya, Wan Ahmad Jaafar (UiTM Cawangan Perlis, 2017)
In this study, the researcher developed an instrument to measure the level of adolescents'knowledge and perceived awareness on cyber-bullying. This instrument is known as the Cyber-bullying Knowledge and Awareness Instrument (CBKAi).Content validity was performed to determine whether the instrument comprises a representative sample of the behaviour domain to be measured. CBKAi was validated by a senior lecturer from a public university who is also an expert in cyber-bullying and also two secondary school counsellors.Apart from that, CBKAi was also tested for its reliability with 30 respondents. The Cronbach's alpha internal consistency reliability coefficient for the instrument is 0.919 for items that are related to knowledge and 0.810 for items that are related for perceived awareness. The statistics show that CBKAi is a reliable instrument to be utilized to measure knowledge and perceived awareness towards cyber-bullying among adolescents.